Pengaruh Return On Equity Debt To Equity Ratio, dan Dividen Payout Ratio Terhadap Harga Saham Pada Perusahaan Properti & Real Estate Tahun 2018-2022 - Cecep Paqih Fauzan; Dinalestari Purbawati; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2024)
Abstract: The purpose of this research is to analyze the relationship between Return On Equity (ROE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) to stock price. This research is using stock price as a dependent variable. Then, Return On Equity (ROE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) are used as an independent variable. The population of this research is property & real estates companies listed on the Indonesia Stock Exchange during the period 2018 – 2022. By purposive sampling method, there are 6 property & real estate companies were obtained as the sample of this research. The analytical method used in this reseacrh is multiple regression analysis.  The result of this research indicate that Return On Equity (ROE) has a positive and significant effect on stock price. Then, Debt to Equity Ratio (DER) has a negative and significant effect on stock price. Meanwhile, Dividend Payout Ratio (DPR) has insignificant effect on stock price of property & real estate companies in Indonesia during 2018-2022.Keywords: debt to equity ratio; dividend payout ratio; return on equity; stock priceAbstrak: Tujuan penelitian ini adalah menganalisis hubungan Return On Equity (ROE), Debt to Equity Ratio (DER), dan Dividend Payout Ratio (DPR) terhadap harga saham. Penelitian ini menggunakan harga saham sebagai variabel dependen. Sedangkan, ROE, DER, dan DPR digunakan sebagai variabel independen. Populasi penelitian ini adalah perusahaan properti & real estate yang terdaftar di Bursa Efek Indonesia  selama periode 2018 – 2022. Dengan metode purposive sampling diperoleh 6 perusahaan properti & real estate sebagai sampel penelitian ini. Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi berganda. Hasil penelitian ini menunjukkan bahwa ROE berpengaruh positif dan signifikan terhadap harga saham. Selain itu, DER juga berpengaruh negatif dan signifikan terhadap harga saham. Sementara itu, DPR tidak berpengaruh signifikan terhadap  harga saham pada perusahaan properti & real estate di Indonesia tahun 2018-2022.Kata Kunci: Debt to Equity Ratio; Dividend Payout Ratio; Harga Saham; Return on Equity